PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIBERI PEKERJAAN RUMAH SECARA KUMULATIF DENGAN NON KUMULATIF DI SDN 147 PEKANBARU - Anggia Gusti Maulana; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find the difference of Mathematics achievement thought by cumulative homework and non-cumulative homework in SD Negeri 147 Pekanbaru. The design used in this research is quasi experimental design. The sample of this research are students of the fourth grade C and D in SD Negeri 147 Pekanbaru. The class C used as the experimental class of cumulative homework while the class A as the control class non-cumulative homework. The data collection technique is test. The Result of data analysis technique shows that two of sample has normal distribution value and data is homogeny. The result of the research shows that the hypothesis which stated that the achievement of Mathematics using cumulative homework was higher than using non-cumulative homework is accepted. It was proven by the mean score of the experimental as 78,28 and control class as 75,60. The difference is 2,68.Key Words: Cumulative Homework, Non-cumulative Homework, Mathematics Achievement